Ginsenoside Rg3 Alleviates ox-LDL Induced Endothelial Dysfunction and Prevents Atherosclerosis in ApoE−/− Mice by Regulating PPARγ/FAK Signaling Pathway - Geng, Jianan; Fu, Wenwen; Yu, Xiaofeng; Lu, Zeyuan; Liu, Yanzhe; Sun, Mingyang; Yu, Ping; Li, Xin; Fu, Li; Xu, Huali; Sui, Dayun (Frontiers in Pharmacology, 2020)
The initiation of atherosclerosis (AS) induced by dyslipidemia is accompanied by endothelial dysfunction, including decreased healing ability and increased recruitment of monocytes. Studies showed ginsenoside Rg3 has potential to treat diseases associated with endothelial dysfunction which can protects against antineoplastic drugs induced cardiotoxicity by repairing endothelial function, while the effect and mechanism of Rg3 on dyslipidemia induced endothelial dysfunction and AS are not clear. Therefore, we investigated the effects of Rg3 on oxidized low density lipoprotein (ox-LDL) induced human umbilical vein endothelial cells (HUVECs) dysfunction and high-fat diets (HFD) induced atherosclerosis in ApoE–/– mice, as well as the mechanism. For in vitro assay, Rg3 enhanced healing of HUVECs and inhibited human monocytes (THP-1) adhesion to HUVECs disturbed by ox-LDL, down-regulated focal adhesion kinase (FAK)-mediated expression of vascular cell adhesion molecule 1 (VCAM-1) and intercellular adhesion molecule 1 (ICAM-1); restrained the FAK-mediated non-adherent dependent pathway containing matrix metalloproteinase (MMP)-2/9 expression, activation of nuclear factor-kappa B (NF-кB), high mRNA levels of monocyte chemotactic protein 1 (MCP-1) and interleukin 6 (IL-6), besides Rg3 up-regulated peroxisome proliferators-activated receptor γ (PPARγ) in ox-LDL-stimulated HUVECs. GW9662, the PPARγ-specific inhibitor, can repressed the effects of Rg3 on ox-LDL-stimulated HUVECs. For in vivo assay, Rg3 significantly reduced atherosclerotic pathological changes in ApoE–/– mice fed with HFD, up-regulated PPARγ and inhibited activation FAK in aorta, thus inhibited expression of VCAM-1, ICAM-1 in intima. We conclude that Rg3 may protect endotheliocytes and inhibit atherosclerosis by up-regulating PPARγ via repressing FAK-mediated pathways, indicating that Rg3 have good potential in preventing dyslipidemia induced atherosclerosis.